Increase in motility and invasiveness of MCF7 cancer cells induced by nicotine is abolished by melatonin through inhibition of ERK phosphorylation. Issue 4 (8th March 2018) - Proietti, Sara; Catizone, Angela; Masiello, Maria Grazia; Dinicola, Simona; Fabrizi, Gianmarco; Minini, Mirko; Ricci, Giulia; Verna, Roberto; Reiter, Russel J.; Cucina, Alessandra; Bizzarri, Mariano
Abstract: Through activation of the ERK pathway, nicotine, in both normal MCF‐10A and low‐malignant breast cancer cells (MCF7), promotes increased motility and invasiveness. Melatonin antagonizes both these effects by inhibiting almost completely ERK phosphorylation. As melatonin has no effect on nonstimulated cells, it is likely that melatonin can counteract ERK activation only downstream of nicotine‐induced activation. This finding suggests that melatonin hampers ERK phosphorylation presumably by targeting a still unknown intermediate factor that connects nicotine stimulation to ERK phosphorylation. Furthermore, downstream of ERK activation, melatonin significantly reduces fascin and calpain activation while restoring normal vinculin levels. Melatonin also counteracts nicotine effects by reshaping the overall cytoskeleton architecture and abolishing invasive membrane protrusion. In addition, melatonin decreases nicotine‐dependent ROCK1/ROCK2 activation, thus further inhibiting cell contractility and motility. Melatonin actions are most likely attributable to ERK inhibition, although melatonin could display other ERK‐independent effects, namely through a direct modulation of additional molecular and structural factors, including coronin, cofilin, and cytoskeleton components.